CASE STUDY ON OPERATION MANAGEMENT PERFORMANCE IMPROVEMENT OF SCRAP IRON COMPANY - Lin, Chin-Chiuan; Huang, Mei-Ya (International Journal of Application on Economics and Business, 2024)
The present study wants to improve the operation management performance, so as to increase the amount of revenue and improve the delivery cost of the case company. Therefore, the purpose of the present study, first, is to analyse the factors that affected the willingness to resupply of suppliers, and adopts the questionnaire survey method to collect data and uses statistical software to analyse the suppliers. Results shows the willingness to resupply of the suppliers. There are 92% suppliers will supply to case company again, and 88% suppliers would recommend peers to supply to case company. Second, use break-even analysis to analyse the delivery cost, compare the distance of the three major steel plants and the number of trips, and propose different delivery car options, which can save nearly NT$ 1.2 million per year for the case company.